Is There Authoritative Voice in Ewok Talk?: On Postmodernism, Fieldwork, and the Recovery of Unintended Meanings - Calkowski, Marcia S. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1991)
Postmodernism emphasizes perspectivism, celebrates indeterminacy, and abjures the authoritative voice. Understanding is to be gained dialogically and achieved through participation and performance, activities often synonymous with anthropological fieldwork. However, fieldwork entails the recovery of unintended as well as intended meanings which are, in turn, invariably situated in a hermeneutical hierarchy. This paper points up the inevitability of constructing such a hierarchy by addressing the problem of voice and meaning in the electronically mediated communication that is Ewok speech. Ewoks are fantasy creatures whose heroic manoeuvres figure significantly in the film Return of the Jedi and who are accidental speakers of Tibetan.